Pelatihan Membangun Komunikasi Artifaktual Pada Siswa SMA - Roswita Oktavianti; Septia Winduwati; Lydia Irena (Jurnal Gema Ngabdi, 2020)
Artifactual communication is a kind of non-verbal communications. The message of artifactual is revealed through physical appearance such as attire and cosmetics. Both of them can create physical attractiveness, self-image and individual personality. Adolescent often have difficulty in accepting their physical bodychanges though some of them are satisfied with their body. In this case, senior high-schools have a social and moral responsibility in order to observe their students who are in adolescence by adjusting the eduction in the class. The team of community service of Faculty of Communication of Universitas Tarumanagara along with SMAN 2 West Jakarta provided a training about the importance of artifactual communications as a kind of non-verbal communications. The aim of this event is to increase the student’s understanding, especially young women, about the importance of artifactual messages through facial appearance. It will helps student increasing their confidence. Based on data gathering by questionnaire, it shows that students recognize, have knowledge and understanding, as well as able to identify objects of artifactual communication. Further, giving material along with practical method are effective way to provide understanding in terms of artifactual communications